Upgrading Slum Area, Development and Hidden Inequality (Case Study: Kampung Warna-Warni and Kampung Tridi) - Alfian, Faqih; Akbar, Taufik (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2020)
The existence of injustice and inequality in access to the development results of the city. Slum areas have become one of the problems that exist in urban life. This automatically occurs as a result of a normal process called urbanization and development. Where many residents end up occupying non-residential areas due to their limited access. Seeing from the perspective of the access theory, how people live in the area is a form of their right to be able to utilize natural resources. One of these uses is used as a place to live. This study used a qualitative descriptive method, by taking several samples as a source of interviews. The arrangement of the slum area is now moving to another dimension, which is no longer forced evictions, but how to organize and change the residential area to be habitable. There are several indicators used in seeing a residential area that is said to be unfit for habitation. Upgrading slum areas have been able to change areas that were previously unfit to be better and able to meet indicators of the feasibility of residential areas in general. This step is also how the community continues to strive to gain access to the area. Kampung Jodipan and Kampung Tridi have changed their appearance, and have improved the quality of their living environment, with tidier, cleaner, and more affordable access to public services. Apart from the results of this research, there are still some problems, one of which is the uncertainty of land rights, so that they will not know the future of the area they live in now. The guarantee of land ownership is important to fight for equal rights to state services, state recognition, and the right to live in the area.